Expression and Subcellular Location of a Leucine Aminopeptidase of Mycoplasma Gallinarum - Wan, X.; Branton, S.L.; Hughlett, M.B.; Hanson, L.A.; Pharr, G.T. (International Journal of Poultry Science, 2003)
Mycoplasma Gallinarum is a commensal with a host range that includes most poultry. This property of M. gallinarum may reflect unique mechanisms for colonization and persistence in various hosts. In previous studies a leucine aminopeptidase (LAP) gene candidate was cloned from a M. gallinarum recombinant genomic library and characterized. Here we evaluate the LAP gene from M. gallinarum at the protein level. A recombinant fusion protein was purified and employed as an antigen to immunize chickens to obtain polyclonal anti-LAP serum. The antiserum was utilized to identify the subcellular location by immuoblotting with Triton X-114 partitions of M. gallinarum proteins. Our results of these experiments show that the LAP gene product is located in the cytoplasmic fraction of the M. gallinarum cell.